LANGUAGE POLITENESS IN THE NOVEL GEEZ AND ANN BY RINTIK SEDU - Zakaria Kreswantono (Jurusan Sastra Indonesia, 2022)
This study aims to describe the form of politeness in the novel Geez And Ann by Rintik Sedu. This research is a qualitative research using document analysis method. Data collection using document study techniques. Data analysis used content analysis techniques. Data sourced from the novel Geez and Ann in the form of words, phrases, and sentences. The results of the study indicate that the use of politeness in language is often done because the speech participants already know and try to show their attention with sympathy.